LEGAL REGULATION OF BLOCKCHAIN TECHNOLOGY IN UZBEKISTAN: CHALLENGES, GAPS, AND PROSPECTS FOR IMPROVEMENT - Boboqulov, S.B.; Shehrozbek Sayfiddinovich, Saidmuratov (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2025)
Objective: To investigate the legal regulation of blockchain technology in Uzbekistan, identify key regulatory gaps and challenges, and propose policy recommendations for a cohesive national blockchain strategy aligned with international best practices. Method: This study employs a qualitative research approach, integrating in-depth interviews, case studies, and document analysis. It examines the legal implications of blockchain adoption, focusing specifically on issues related to privacy, intellectual property protection, and cross-border regulatory complexities. Results: The findings indicate that Uzbekistan currently lacks a comprehensive legal framework for blockchain regulation. This regulatory deficiency hampers the technology's integration into critical sectors such as finance, public administration, and land registration, thereby impeding innovation and ethical implementation. Novelty: This research contributes to the emerging discourse on blockchain governance by providing a detailed analysis of the unique challenges faced by Uzbekistan. It offers novel policy recommendations aimed at enhancing legal clarity and fostering an environment conducive to the effective and compliant use of blockchain technology.